2002
DOI: 10.1161/hq0102.102190
|View full text |Cite
|
Sign up to set email alerts
|

Folates and Cardiovascular Disease

Abstract: Abstract-It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
171
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(185 citation statements)
references
References 141 publications
5
171
0
9
Order By: Relevance
“…16 Additionally, folates may facilitate the binding of tetrahydrobiopterin to eNOS. 15,16 Finally, it has been speculated that 5-methyltetrahydrofolate may mimic tetrahydrobiopterin at its receptor site on eNOS or may facilitate the electron transfer to produce NO. 15,27 There are certain limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Additionally, folates may facilitate the binding of tetrahydrobiopterin to eNOS. 15,16 Finally, it has been speculated that 5-methyltetrahydrofolate may mimic tetrahydrobiopterin at its receptor site on eNOS or may facilitate the electron transfer to produce NO. 15,27 There are certain limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 In fact, 5-methyltetrahydrofolate, the active metabolite of folic acid, may have direct effects on uncoupled eNOS, which results in increased release of NO and decreased release of superoxide anion. 13,15,16 Thus, there may be a rationale for considering the use of folates to restore NO availability in situations such as diabetes where there is a relative deficiency of active tetrahydrobiopterin. Indeed, van Etten et al 17 demonstrated that an acute arterial infusion of 5-methyltetrahydrofolate could restore impaired endothelium-dependent vasodilatation as assessed by forearm plethysmography in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Folic acid and its metabolites are also superoxide radical scavengers. 34,35 The Role of PSMA in Vasculogenesis Cellular folate gradients across cell membranes are maintained by the g-glutamylated form, polyglutamyl folate, which accumulates intracellularly, and must be deconjugated by pteroylpoly-g-glutamate hydrolase, also called folate hydrolase, into a monoglutamylated form to participate in metabolic reactions. 36 PSMA has folate hydrolase activity.…”
Section: Psma Expression In Tumor Neovasculaturementioning
confidence: 99%
“…Guo et al15 found that FA therapy could significantly improve endothelial function. Most studies of the relationship between FA and atherosclerosis have focused on FA's ability to reduce serum homocysteine levels 24 or on FA's antioxidant,7 anti‐inflammatory11 and antithrombotic effects 14. Little is known regarding the regulatory effects of FA on VSMC dedifferentiation, which is necessary for the development and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%